2016
DOI: 10.1186/s40560-016-0152-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the recovery time of continuous normal voltage in amplitude-integrated electroencephalography in out-of-hospital cardiac arrest patients treated with therapeutic hypothermia: a retrospective study

Abstract: BackgroundThe early prediction of neurological outcomes in postcardiac arrest patients treated with therapeutic hypothermia (TH) remains challenging. Amplitude-integrated electroencephalography (aEEG) is a type of quantitative EEG. A particular cutoff time from the return of spontaneous circulation (ROSC) to the recovery of a normal aEEG trace for predicting a good neurological outcome has not yet been established. The purpose of the present study was to examine the relation between neurological outcomes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…This is also reflected by the fact that more than 10% of participants of the survey skipped the question about which classification they use for interpretation. A modified version of a neonatal classification (by Hellström-Westas) has been used in adults after cardiac arrest (18)(19)(20)(21)29). In accordance with these results, PICU staff almost equally often interpreted the raw EEG curve and used the classification by Hellström-Westas.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is also reflected by the fact that more than 10% of participants of the survey skipped the question about which classification they use for interpretation. A modified version of a neonatal classification (by Hellström-Westas) has been used in adults after cardiac arrest (18)(19)(20)(21)29). In accordance with these results, PICU staff almost equally often interpreted the raw EEG curve and used the classification by Hellström-Westas.…”
Section: Discussionmentioning
confidence: 72%
“…It is also a valuable method for neonates with brain lesions and severe infections (8)(9)(10)(11) as well as for preterm infants for the prediction of outcome (12)(13)(14)(15). Also in adult intensive care, interest in aEEG is increasing recently (16)(17)(18)(19)(20)(21). Its great advantage is that it can be operated and evaluated by the PICU team, independent from an epileptologist.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported that the presence of a normal aEEG trace within 24 hours is a predictor of good neurological outcome after cardiac arrest. 5,8 In a prospective study that included 130 comatose cardiac arrest survivors, Oh et al 5 reported that the presence of a normal trace within 24 hours predicted a good neurological outcome with a positive predictive value of 88.1%.…”
Section: Discussionmentioning
confidence: 99%
“…aEEG is easily interpreted by intensivists and emergency physicians at the bedside. Recently, the pattern of aEEG after return of spontaneous circulation (ROSC) has been reported to be useful for predicting neurological outcomes in adult patients post cardiac arrest [ 7 9 ]. The early recovery of a normal pattern of aEEG after ROSC is reported to be a predictor of good neurological outcome.…”
Section: Introductionmentioning
confidence: 99%